Antidiabetic and biological effects of hydro-methanolic extracts from Dioscorea alata L and D. rotundata Poir (Dioscoreaceae) tubers in alloxanized guinea pigs - Raphaël Lombe Mputu; Desiré Muganza Musuyu; Jeff Bekomo Iteku; Odette Ngandu Kabena; Jean-Pau (Orapuh, Inc., 2024)
Introduction The use of medicinal plants is common in healthcare systems globally, often involving the therapeutic use of food plants, especially in areas where traditional medicine is integral to healthcare. Purpose This study aims to evaluate the antidiabetic, hypolipidemic, and biological effects of Dioscorea alata and D. rotundata on liver enzyme activity and kidney function, with potential applications for diabetes management in resource-limited settings. Methods Forty guinea pigs were induced with diabetes using alloxan monohydrate and divided into eight groups. Four groups were treated with hydro-methanolic extracts of Dioscorea alata and D. rotundata tubers at different doses for 21 days. A negative control group received distilled water, while diabetic control groups were given a water placebo. Two diabetic groups were treated with standard anti-diabetic drugs: slow insulin and glibenclamide. Data analysis included various statistical tests, such as Student's t-test, ANOVA, and Kruskal-Wallis, with significance set at p < 0.05. Results Dioscorea rotundata at 400 mg/kg was most effective, significantly reducing blood glucose levels by 59.46% to 122.8 mg/dL, compared to a 24.12% increase in the diabetic control group (413.5 mg/dL). This extract also improved lipid profiles, lowering triglycerides by 42.41% to 139.76 mg/dL, total cholesterol by 39.94% to 101.52 mg/dL, and LDL-cholesterol by 40.93% to 65.02 mg/dL, while increasing HDL-cholesterol by 34.84% to 31.54 mg/dL. Additionally, D. rotundata improved liver and kidney function, reducing ALAT levels by 36.16% to 53.64 IU/L, ASAT levels by 7.45% to 209.44 IU/L, and creatinine by 75.41% to 0.88 mg/dL. Conclusion Dioscorearotundata at 400 mg/kg shows the most pronounced beneficial effects in managing diabetes and improving metabolic and organ functions in the studied guinea pigs.